Solar Drying Technology in Indonesia: an Overview - Ahmad Fudholi; Abrar Ridwan; Rado Yendra; Ari Pani Desvina; Hartono Hartono; Majid Khan Bin Majahar Ali; Tri Suyono; Kamaruzzaman Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The most important benefit of solar energy is renewable and low pollutant source of energy (clean energy). Solar energy technology and research are developing fast and much of the technology needed for these applications in industry and agricultures is already available. Solar drying technology (SDT) is one of the most attractive and promising applications of solar energy technology. In this paper, the various performances of SDTs in Indonesia are summarized with details. Generally, the cabinet-type and tunnel-type SDTs are remarkably well suited to drying small quantities of vegetables and fruit on the household scale. Greenhouse and hybrid SDTs are suitable for use on a large scale by industries.